Big Coal : Australia's Dirtiest Habit. - Pearse, Guy (University of New South Wales Press, 2013)
A look at the underbelly of an industry whose power continues to soar even as its expansion feeds catastrophic climate change, this work dissects the Australian coal industry's influence to publicly, and behind closed doors, get its way. The book exposes the myth of clean coal and the taxpayer-funded public relations machine behind it while laying bare the desolation in regional Australia as prime farming land, the fabric of communities, and much else is stripmined along with the coal. Most contentiously of all, Big Coal explores how Australia can break its dirtiest habit and move to a far mor.